Libraries of the world during the pandemic: a new experience and the first conclusions - Asuman Akdemir; Aglaé Achechova; Benjamin Guichard; Andrey E. Guskov; Assel Lakhayeva; Anna Rakityanskaya; Natalya S. Redkina; Alla Roylance; Galina N. Serbina; Olga Einasto; Inna Yuryk (Библиосфера)
The main theme of 2020 for libraries around the world is organizing the work under the constraints associated with COVID-19, which was confirmed by the results of information searches for articles in the world’s largest databases (Google Scholar, Web of Science, Scopus, etc.), which discuss actual problems of libraries’ activity during this period. Their solution is achieved by developing common approaches to challenges at the global level, sharing best practices and methods of working in a pandemic. The purpose of the article is to present the key reports presented in the cycle of online meetings entitled “Life of the world’s libraries during a pandemic”, organized by the State Public Scientific and Technological Library of the Siberian Branch of Russian Academy of Science (SPSTL SB RAS). The article presents the experience of foreign and Russian libraries: Bibliothèque universitaire des langues et civilisations (France), the Libraries of New York University and Harvard Universities (USA), University of Tartu Library (Estonia), the National Library of the Republic of Turkey, the Scientific Library of the Belarusian National Technical University, Research Library of Tomsk State University and SPSTL SB RAS. The authors showed the activities of libraries to organize the work of employees and service users. As a result, it was determined that libraries choose different ways and methods of working with users, develop innovative services, expand the repertoire of information resources / products, take measures to ensure the safe work of employees, including remotely. It was emphasized that not all types of work could be transferred to a remote mode, and that required quick decisions on the redistribution of functions among employees and the мlaunch of new projects. It is concluded that librarians need to continue learning digital etiquette and gaining new skills and competencies for telecommuting.